(untitled) (Scientific journal of the Fergana State University, 2023)
This article describes the solution of organizational and pedagogical problems of educational and pedagogical practice, its didactic aspects, the development of a teacher-mentorʼs work plan and methods of its implementation when creating an educational and methodological complex for the organization of educational and pedagogical practice, the correct organization of pedagogical practice and the elimination of problems and other issues.